PENGENDALIAN SISTEM PENCUCI DAN PENGERING TANGAN OTOMATIS MENGGUNAKAN SENSOR PASSIVE INFRA RED (PIR) - Taufik Rahman; Deny Wiria Nugraha; Yusuf Anshori (MEKTRIK, 2015)
Washer and dryer hand automatic system is one of the few applications of control systems. Research on control system washer and dryer hand automatic is aimed to know the working principle and how to implement sensors Passive Infra Red (PIR) as detection sensors, microcontroller ATMega32 as the main controller and Selenoid Valve, Dryer and Liquid Crystal Display (LCD) as an output device into a system that can be controlled automatically so that the activities of hand washing and drying can be done easily and practically. This research conducted with qualitative methods based on experiment which will be designed a washing system and automatic hand dryer using a PIR sensor-based microcontroller ATMega32. Washer and dryer hand automated system operate based on reaction Passive Infra Red sensor (PIR) on the human body, namely the hands of users. If one of the three mode buttons have been pressed and the user's hand is detected by the PIR sensors located around the faucet then the sensor will provide a response to the microcontroller to manage the data that will instruct the output device to work automatically.